2016
DOI: 10.1093/infdis/jiw413
|View full text |Cite
|
Sign up to set email alerts
|

Human Alveolar Macrophages May Not Be Susceptible to Direct Infection by a Human Influenza Virus

Abstract: The current studies were undertaken to determine the susceptibility of human alveolar macrophages (AMs) to influenza A virus (IAV) infection in comparison with autologous peripheral blood-derived monocytes-macrophages (PBMs). AMs and PBMs were exposed to IAV in vitro and examined for their ability to bind and internalize IAV, and synthesize viral proteins and RNA. PBMs but not AMs demonstrated binding and internalization of the virus, synthesizing viral proteins and RNA. Exposure of AMs in the presence of a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…PBM, as expected, bound and internalized IAV and synthesized viral RNA and proteins. In contrast, AM showed no evidence of IAV infection despite equivalent exposure [2]. The AM did become infected and synthesize IAV proteins if the cells were exposed to the virus in the presence of a sialidase inhibitor or an anti-IAV antibody or, in the case of exposure to a fluorescein isothiocyanate-labeled IAV, in the presence of anti-fluorescein isothiocyanate antibody.…”
Section: Unexpected Findings Regarding Interactions Of Human Alveolarmentioning
confidence: 85%
See 2 more Smart Citations
“…PBM, as expected, bound and internalized IAV and synthesized viral RNA and proteins. In contrast, AM showed no evidence of IAV infection despite equivalent exposure [2]. The AM did become infected and synthesize IAV proteins if the cells were exposed to the virus in the presence of a sialidase inhibitor or an anti-IAV antibody or, in the case of exposure to a fluorescein isothiocyanate-labeled IAV, in the presence of anti-fluorescein isothiocyanate antibody.…”
Section: Unexpected Findings Regarding Interactions Of Human Alveolarmentioning
confidence: 85%
“…The AM did become infected and synthesize IAV proteins if the cells were exposed to the virus in the presence of a sialidase inhibitor or an anti-IAV antibody or, in the case of exposure to a fluorescein isothiocyanate-labeled IAV, in the presence of anti-fluorescein isothiocyanate antibody. Thus, human AM are not susceptible to direct infection by IAV but can be infected when exposed to the virus complexed with an antibody [2].…”
Section: Unexpected Findings Regarding Interactions Of Human Alveolarmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that the most human influenza viruses predominantly infect the upper airways (we do not consider in this part of the study avian influenza and pneumonia) (van Riel et al, 2007;Ettensohn et al, 2016). We suggested that the first step of virus infections is the deposition of viruses on the epithelial cells of upper airways (see remark below #about virus attach).…”
Section: Upper Airways Are Target Area Of Influenza Viruses: Is It Anmentioning
confidence: 99%
“…Human influenza viruses attached more strongly to human trachea and bronchi (van Riel et al, 2007;Ettensohn et al, 2016). Most strains of rhinovirus and the common cold virus, replicate better in the nasal cavity (Foxman et al, 2015;.…”
Section: (About Virus Attach)mentioning
confidence: 99%